2020
DOI: 10.1177/2150132720931345
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Using a Pocket-Sized Ultrasound Device to Measure the Inferior Vena Cava Diameter of Patients With Heart Failure in the Community Setting: A Pilot Study

Abstract: Background: The incidence of heart failure as well as its treatment costs and rehospitalization rates are increasing worldwide. Physical assessment of elderly patients with heart failure living in their homes is challenging for community nurses. Pocket-sized echocardiographs will be useful for assessing the condition of the patients with heart failure during home-visit care. Objectives: This pilot study aimed to examine the feasibility of measuring the inferior vena cava (IVC) diameter using a pocket-sized ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Although there are still many challenges ahead (e.g. relatively low accuracy of the measurement) (Antipova et al, 2021;Kimori & Tamura, 2020), several studies included in this review also demonstrated that nursing students could acquire various PoCUS skills to some degree through training, such as sonographic measurement of inferior vena cava diameters, residual urine volume, rectus abdominis muscle width, imaging vital organs, and breast imaging for early detection of breast cancer. There are some other PoCUS skills that are not included in the review but are used in clinical practice by nurses, such as assessing respiratory conditions, constipation, deep venous thrombosis, and pressure ulcers (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…Although there are still many challenges ahead (e.g. relatively low accuracy of the measurement) (Antipova et al, 2021;Kimori & Tamura, 2020), several studies included in this review also demonstrated that nursing students could acquire various PoCUS skills to some degree through training, such as sonographic measurement of inferior vena cava diameters, residual urine volume, rectus abdominis muscle width, imaging vital organs, and breast imaging for early detection of breast cancer. There are some other PoCUS skills that are not included in the review but are used in clinical practice by nurses, such as assessing respiratory conditions, constipation, deep venous thrombosis, and pressure ulcers (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…No adjunctive or specific training is required. (3) Adoption by non-physicians users: Trained nurses may successfully use US for IVC assessment [47]. Thus, IVC edge tracking echocardiography may be easily managed by nurses, giving them more autonomy and personal skills.…”
Section: Rap As a Marker Of Congestion: Current Advanced Technique Of...mentioning
confidence: 99%
“…Portable US devices have passed through three generations: Laptop-associated devices (personal computer-sized machine coupled with multiple applications), hand-carried devices (book-sized machine carried by hand), and hand-held devices (portable and able to fit in the pocket of a clinician’s white coat, thus referred to as pocket-sized US). Each US company has different built-in applications, such as Doppler display, puncture guidance, and distance or volume measurement[ 16 ].…”
Section: The Pocket-sized Us Education Seminarmentioning
confidence: 99%
“…Each US company has different built-in applications, such as a Doppler display (Figures 2 and 5 ), embedded in almost all devices. Puncture guidance is embedded in about half of all devices[ 25 ], and distance or volume measurement function is embedded in a small number of devices (Figure 13 )[ 16 , 26 ]. Biplane imaging is embedded in a limited number of devices[ 27 ], and wireless function is embedded in a small number of devices (Figure 14 ).…”
Section: Half-day Lecturementioning
confidence: 99%
See 1 more Smart Citation